The Effect of Eavesdropping and Wormhole Attacks on Mobile Ad Hoc Network - Al-Safwani, Nadher Mohammed Ahmed (2009)
Security has become the main concern to grant protected communication between mobile nodes in an unfriendly environment. Wireless Ad Hoc network might be unprotected against attacks by malicious nodes. This project evaluates the impact of some adversary attacks on mobile Ad Hoc network system (MANET's) which have be tested using QualNet simulator. Moreover, it investigates the active and passive attack on mobile Ad Hoc network. At the same time, it measures the performance of MANET with and without these attacks. The simulation is done on data link layer and network layer of mobile nodes in wireless Ad Hoc network. The results of this evaluation are very important to estimate the deployment of the Mobile Ad Hoc nodes for security. Moreover, this study have been analyzed the performance of MANET and perform 'what-if' analyses to optimize them.